INTRODUCTION TO SPECIAL ISSUE 2 : 2017 - Omar, Dasimah; Ling Hoon Leh, Oliver (PLANNING MALAYSIA, 2017)
The urban planning system seeks to guide appropriate development to the right place and to prevent inappropriate development from taking place aiming at securing sustainable development. However, rapid urban growth due to high fertility and rural-urban migration have exerted pressure on the environment of urban settlements. Urban settlements in developing countries, especially, are facing increasing issues and challenges in various aspects, i.e. physical, social and economic. In Malaysia, various researches and studies have been carried out to understand the issues and challenges of urban settlements in the country. This issue of Planning Malaysia aims to share findings of researches/studies in various aspects of urban settlement and planning in Malaysia. It covers the aspects of globalization and urban planning, urban forms, finance, housing, social, agro-tourism, recreation, urban spaces, transportation, and heritage. The authors of paper 1 suggest that neoliberal globalization certainly gives rise for enabling urban settlements as can be seen in the area of Kuala Lumpur and Selangor. However, the process brings further challenges to the Malaysian planning system such as social injustice and environmental deterioration. In paper 2, the study on urban sprawl has found that cost of development is higher when built further away from service centres. The substantial infrastructure costs savings can be achieved by increasing urban densities and locating new development near existing built-up areas. In paper 3, the authors highlighted the efforts by the government to eradicate squatters and providing low-cost housing in Malaysia. However, the existing policies and programs have yet to meet the target of “zero squatter”. For social-related issues, paper 4 concludes that most of the local respondents from one of the medium cost apartments felt that the presence of foreign immigrants negatively affecting them in terms of family and community relationship, sense of belonging, safety and housing price/cost. In paper 5, the authors discuss several negative and positive impacts on locals due to the presence of foreign immigrants in agro-tourism industry in Cameron Highland. In terms of recreational planning in urban settlements, paper 6 shows that recreational facilities in urban areas can give satisfaction to youths. It covers the aspects of the current state of the facilities, proximity, accessibility and level of maintenance. Meanwhile, paper 7 indicates that the nature and human interactions require elements of open spaces such as green spaces, water elements, and physical attributes to enhance the human-human and human-nature interactions. For the aspect of transportation, paper 8 found that majority of respondents were not ready to consider cycling or walking as an alternative mode of travel. Besides, respondents who use their cars more frequently have lower level of willingness to use public transport. Further, the authors of paper 9 also found that majority of respondents did not use bicycles as a primary mode of transportation in their daily trips to work, shops, and others even though the provision of cycle lanes and the related infrastructure were excellent. In paper 10, the authors look into public transportation service (Hop-On Hop-Off bus) for urban tourism. It was found that the single route bus service for whole Kuala Lumpur city centre is not suitable. It takes tourists too long to complete the route. The authors propose that the existing route should be broken into three. For the issues on heritage, paper 11 shows that gentrification is a decent way of developing an urban heritage site to be in line with the development strategies of a country. However, uncontrolled gentrification can result in negative consequences. In the study area, many members of the local community felt marginalized and isolated in their place of birth. Finally, it should be mentioned that the publication of this Planning Malaysia Journal is aimed at encouraging professional/academic communication and sharing of research findings among practitioners, policy makers, researchers, students, and managers in urban development and planning related fields. Continuous research, study, and sharing of knowledge should be able to improve the existing practice of planning, design, and management of urban settlements.